The Role of Tourism Marketing Strategies in Achieving a Competitive Advantage for Tourism Organizations (An Analytical Study of the Opinions of a Sample of Employees in some Excellent Hotels in Baghdad): Peran Strategi Pemasaran Pariwisata dalam Mencapai Keunggulan Kompetitif bagi Organisasi Pariwisata (Studi Analitis terhadap Pendapat Sebagian Karyawan di Beberapa Hotel Unggulan di Baghdad) - Dr. Khaleel Ibrahim Breesam Breesam (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Tourism marketing strategies play a central role in shaping the performance and competitiveness of tourism institutions in a dynamic global environment. Specific Background The study focuses on how structured marketing strategies are applied within tourism organizations to support sectoral development and organizational positioning. Knowledge Gap Previous studies have not sufficiently clarified the relationship between strategic marketing practices and competitive positioning within specific regional tourism contexts. Aims This research aims to examine the role of tourism marketing strategies in achieving competitive advantage and supporting sector growth. Results The findings indicate that well-designed marketing strategies contribute to improved organizational positioning, customer engagement, and sector development. Novelty The study provides an integrated perspective linking marketing strategy dimensions with competitive outcomes in the tourism sector. Implications These results suggest that tourism institutions should adopt comprehensive and adaptive marketing strategies to strengthen their competitive positioning and sustain sectoral growth. Keywords: Tourism Marketing, Competitive Advantage, Strategic Management, Tourism Sector, Marketing Strategy Key Findings Highlights Structured planning supports stronger organizational positioning Customer-oriented approaches shape market competitiveness Strategy integration aligns with sector development goals